The mostly true adventures of Homer P. Figg - Philbrick, W. R. (W. Rodman) (Blue Sky Press, 2009)
Homer P. Figg escapes from his wretched foster home in Pine Swamp, Maine, and sets out to find his beloved older brother, Harold, who has been illegally sold into the Union Army.